A crude methanolic extract from the parotoid gland secretion of Rhaebo guttatus stimulates the production of reactive species and pro‑inflammatory cytokines by peritoneal macrophages. (2023) - PELISSARI, SHEILA RODRIGUES DO NASCIMENTO; SOUZA, ELOANA BENASSI RIBEIRO DE; SINHORIN, VALÉRIA DORNELLES GINDRI; RODRIGUES, DOMINGOS DE JESUS; CASTOLDI, LINDSEY; SINHORIN, ADILSON PAULO
No abstract available